Experimental and numerical study of Buoyancy-driven low turbulence flow in rectangular enclosure partially filled with isolated solid blockages. (December 2018) - Iyi, Draco; Hasan, Reaz; Penlington, Roger
Highlights: The effect of isolated blockages proximity on natural convection flow inside an enclosure was investigated. Natural convection inside an enclosure are very sensitive to the proximity of blockages. The Heat transfer becomes very significant when blockages are positioned within the hydrodynamic boundary layer. Blockages proximity can affect the overall heat transfer via flow field. Blockages positioned outside the hydrodynamic boundary layer resulted in 7.6% increase in the heat transfer. Abstract: This paper considers the natural convection inside an air filled enclosure having several isolated cylindrical blockages distributed within it, and arranged parallel to two vertical walls of the enclosure. These two walls are maintained at different temperatures resulting in a natural convection process inside the enclosure. The objectives are to provide experimental temperature data and to investigate the influence of the blockages proximity within and outside the active vertical wall hydrodynamic boundary layer of the natural convection flow and heat transfer. Experiments were designed with high degree of accuracy to provide reliable temperature data-bank for a range of blockages proximity to the active vertical walls. The test enclosure is an air filled rectangular cavity fixed at 0.97 m × 0.4 m × 1 m, corresponding to the height, width and depth respectively. The top and bottom walls are conducting surface and the temperature difference between the active vertical walls was maintained at 42.2 °C resulting in a characteristic Rayleigh number of 4.04 × 10 9 based on the enclosure height. All the walls of the enclosure were insulated externally while the inner surfaces were covered with conducting plate. The test cavity capability of establishing low turbulence natural convection flows was verified. All temperature data were obtained at steady state and it was verified to be reproducible by repeating the experiment at different times. Also, two-dimensionality was verified via rigorous temperature readings over a period of time. Additional temperature readings were recorded for the air and cylinder surfaces at several distinct locations. Further investigations were conducted using a numerical approach to supplement and validate the experiments. Experimental temperature data collated at various locations within the enclosure show excellent comparison with numerical results and as such provide a useful experimental benchmark temperature data for the validation of low turbulence natural convection flow in enclosure partially filled with isolated solid objects. Our result shows that a significant increment or reduction in air temperature and wall heat transfer could be achieved by varying the blockages proximity, and especially when the blockages are positioned within the hydrodynamic boundary layers of the active vertical walls.